THE EFFECT OF TRAINING AND MOTIVATION ON THE PERFORMANCE OF EMPLOYEES OF THE BPBD (REGIONAL DISASTER MANAGEMENT AGENCY) POST IN TANJUNG BATU, BERAU, EAST KALIMANTAN, INDONESIA - Aziz, Wardah Warsimah; Hakim, Abdul; Suryadi, Suryadi (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study examines the impact of training and motivation on the performance of employees at the Tanjung Batu BPBD Post in Berau Regency, Indonesia. Employing a quantitative approach, the research explores how structured training programs and motivational strategies contribute to enhancing employee effectiveness in disaster management organizations. The findings reveal that both training and motivation positively influence employee performance, with intrinsic motivation playing a particularly important role in strengthening engagement and commitment to organizational goals. Moreover, the combination of training and motivation demonstrates a synergistic effect, highlighting the importance of integrating competency development and motivational strategies to improve organizational responsiveness and effectiveness in disaster-prone regions.